We Heal as One, We Rise as One: The Rise of Community Pantries in the Midst of COVID-19 Pandemic in Northern Philippines - Ederlyn Bautista; Krisha Mae Narag; Darin Jan Tindowen; Cirilo Parallag Jr (Formosa Publisher, 2023)
Many Filipinos, especially those from the poorest sectors, have struggled to secure their livelihoods as a result of the pandemic restrictions, and have gone hungry as a result of food system disruptions and inadequate food help from the local government. Hence, various individuals, private corporations, and organizations have emerged with various initiatives to aid fellow Filipinos in need in an effort to strengthen the current situation and address the challenges posed by the COVID-19 pandemic. The latest Community Pantry Initiatives in different parts of the Philippines are examples of this emergence. Due to this fact, the researchers conducted this study to explore the experiences of community pantry organizers and volunteers in the Mainland Cagayan Valley region. Basic qualitative research design was utilized in this study. Through purposive sampling, a total of 15 informants from the Mainland Cagayan Valley region participated in this study. The data was gathered by engaging in an online interview with the use of open-ended questions. The results revealed three major recurring themes, to wit: (1) Description of Organized Community Pantries among Informants; (2) Reasons for Organizing Community Pantries; and (3) Experiences of Community Pantry Organizers and Volunteers